Implementation of servant leadership at LKP Quali International Surabaya (QIS) - Musyafa’ah, Lili; Kaserero, Subira; Jihan, Farah Nur (LP3M Universitas Islam Zainul Hasan Genggong, 2024)
Servant Leadership is a leadership approach that focuses on service to others. The main characteristics of servant leadership are explained in detail, including a focus on service to Team members and the communities served, the ability to understand and feel the experiences of others, as well as the concepts of leadership by example, empowerment, focus on growth and development, building strong relationships, and collaborative decision making. Apart from that, this text describes the implementation of servant leadership at LKP Quali International Surabaya (QIS) along with the results achieved, including improving the quality of the institution and the awards obtained. Effective implementation of servant leadership has played an important role in creating an inclusive work environment, empowering Team members, and encouraging more holistic and sustainable decision making at LKP QIS. Thus, this text provides a systematic overview of the concept of servant leadership and its positive influence in educational institutions.